THE INFLUENCE OF FINANCIAL LITERACY AND RELIGIOSITY ON STUDENT CONSUMPTIVE BEHAVIOR MEDIATED BY LIFESTYLE - Hatta Setiabudhi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This study was conducted to determine the effect of financial literacy and religiosity on the consumptive behavior of a student with lifestyle as an intervening variable. This type of research is quantitative research. The data used in this study are primary data. Respondents were 54 students at the Nahdlatul Ulama Al Ghazali using a questionnaire. The results of this study indicate that the lifestyle variable and religiosity has an effect on consumptive behavior and also the results of this study indicate that religiosity affects the lifestyle of management students.